GBH (Brazilian Group of Hemochromatosis): educating about the disease to preserve life - Lima, Solange Rosanir de; Nakahara, Jennifer Saori; Bottino, André Machado; Machado, Silmara Rodrigues; Santos, Paulo Caleb Júnior Lima (O Mundo da Saúde, 2024)
Hemochromatosis is a disease that is not widely known among the general population or healthcare professionals, particularly because its signs and symptoms are non-specific, making diagnosis challenging. It is caused by a deficiency of hepcidin, an important hormone responsible for iron homeostasis. Reduced production or activity of this hormone leads to increased intestinal iron absorption, resulting in iron overload in the body and, consequently, damage to various organs. Diagnosis and treatment are essential processes to ensure a better quality of life for patients. In this context, the objective of this university extension is scientific dissemination to promote advances for a more effective and safer treatment and diagnosis for patients. The methods involved using the website of the Brazilian Hemochromatosis Group (GBH) and social media to disseminate knowledge with a simple, didactic approach backed by scientific foundations to reach all interested parties. A Google® Forms questionnaire was also created to gather input for developing educational materials on the most requested topics in stage 1. In stage 2, we conducted a survey on the knowledge and perceptions of individuals who accessed these contents. The main results observed were engagement on social media and the GBH website by healthcare professionals, patients, and their families, who subscribed, followed, and expressed interest in learning more about hemochromatosis, in addition to providing feedback for future improvements to the extension project. Thus, the importance and scientific contribution of this health education model were observed, with the production of accessible, scientifically based materials. Based on feedback from the participants, the positive impact on patients and healthcare professionals from the actions carried out was evident. This enables the planning of new actions and approaches to continue with the purpose of disseminating information in a clear and objective manner, accessible to all.